Inventarisasi Jenis-jenis Amfibi (Ordo Anura) di Areal Lahan Basah Sekitar Danau Sebedang Kecamatan Sebawi Kabupaten Sambas - Tri Rima Setyawati, Rino Saputra, Ari Hepi Yanti (Jurnal Protobiont, 2016)
The Order Anura are members of Amphibians that live in various types of habitats such as terrestrial, aquatic, arboreal and fossorial. This research aims to find out the species of the members of the Order Anura found in the area. Sampling was carried out in April 2015, using the visual encounter survey method combined with the line transect. The transects were made at 6 stations with different environmental settings. The species of the members of the Order Anura found in the wetland area around Sebedang Lake were as many as 10 speciesbelonging to 5 families, namely Dicroglossidae (Fejervarya cancrivora, F. limnocharis, Limnonectes ibonarum and L. paramacrodon), Ranidae (Hylarana erythraea, H. baramica and H. nicobariensis), Megophrydae (Leptobrachium abboti), Microhylidae (Kaloula pulchra) and Bufonidae (Duttaprhynusmelanostictus). Members of the Order Anura the most found in species L. limnocharis as many as 28 individuals and the lowest to a species L. paramacrodon such as 1 individual.